2018
DOI: 10.15171/jcvtr.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

New insights on atherosclerosis: A cross-talk between endocannabinoid systems with gut microbiota

Abstract: The incidence of atherosclerosis is increasing rapidly all over the world. Inflammatory processes have outstanding role in coronary artery disease (CAD) etiology and other atherosclerosis manifestations. Recently attentions have been increased about gut microbiota in many fields of medicine especially in inflammatory diseases like atherosclerosis. Ineffectiveness in gut barrier functions and subsequent metabolic endotoxemia (caused by rise in plasma lipopolysaccharide levels) is associated with low-grade chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…The bacterial metabolite trimethylamine is produced by the gut microbiota from dietary choline, phosphatidylcholine and l ‐carnitine, then oxidized to TMAO in the liver and released into the circulation . It has been suggested that TMAO contributes to atherosclerosis in part by promoting macrophage foam cell formation in atherosclerotic lesions as well as ineffective RCT and disruption of lipid homeostasis . For example, TMAO increased the macrophage expression of SR CD36, thereby promoting the uptake of modified LDL, and reduced the expression of enzymes involved in the synthesis of bile acids that are involved in RCT .…”
Section: Probiotics and Tmaomentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial metabolite trimethylamine is produced by the gut microbiota from dietary choline, phosphatidylcholine and l ‐carnitine, then oxidized to TMAO in the liver and released into the circulation . It has been suggested that TMAO contributes to atherosclerosis in part by promoting macrophage foam cell formation in atherosclerotic lesions as well as ineffective RCT and disruption of lipid homeostasis . For example, TMAO increased the macrophage expression of SR CD36, thereby promoting the uptake of modified LDL, and reduced the expression of enzymes involved in the synthesis of bile acids that are involved in RCT .…”
Section: Probiotics and Tmaomentioning
confidence: 99%
“…[75,76] However, interactions between probiotic bacteria, the gut, and the host immune systems are highly complex and despite increasingly growing clinical evidence, remain poorly understood. [75,76] In a recent study, a reduction in atherosclerotic lesion development was accompanied by the suppression of interferon--producing CD4 + T cells and pro-inflammatory cytokine production in Pediococcus acidilactici R037-treated mice. [45] In addition to a reduction in pro-inflammatory T cells, probiotic bacteria have been shown to decrease inflammation via an increase in regulatory T cells.…”
Section: Probiotics and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous data have supported the contribution of dysbiosis in development of CVD by some mechanisms including increased gut permeability and metabolic endotoxemia [5][6][7]. This can be explained by a microbiome-derived lipopolysaccharide (LPS), a major component of the external membrane in gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with metabolic diseases are shown to be more likely to develop concurrent bacteraemia during dengue which also increased the likelihood of fatal dengue [22]. Therefore, it would be important to determine if low-grade endotoxaemia seen in patients with metabolic diseases [23], contribute to severe dengue and subsequently concurrent bacteraemia.…”
Section: Introductionmentioning
confidence: 99%